IECON 2015 - 41st Annual Conference of the IEEE Industrial Electronics Society 2015
DOI: 10.1109/iecon.2015.7392334
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of an elderly driver behaviour in urban intersections based on a risk potential model

Abstract: This paper proposes a driving safety evaluation method based on the parameter analysis of a driver model. Since the driving abilities, such as reaction, recognition and judgment time decrease with aging, it is difficult for elderly drivers to avoid the traffic accidents instantly. Therefore, the proactive safety driving is important for the elderly drivers to prevent the accidents. Then, the safety evaluation criteria of a driving behavior are useful to encourage the driver to keep proactive safety driving. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that experienced and expert drivers tend to take proactive action to avoid collisions, e.g., by slowing down as they approach an intersection with poor visibility [19,33]. However, it is neither safe nor reasonable to assume that every driver approaching an intersection will behave in this manner.…”
Section: Driver Typesmentioning
confidence: 99%
“…Studies have shown that experienced and expert drivers tend to take proactive action to avoid collisions, e.g., by slowing down as they approach an intersection with poor visibility [19,33]. However, it is neither safe nor reasonable to assume that every driver approaching an intersection will behave in this manner.…”
Section: Driver Typesmentioning
confidence: 99%
“…Analyzing driving behaviors is a sophisticated task, since drivers' maneuvering pattern can be affected by many factors such as road environment (e.g., intersection or traffic congestion) and driver categories (e.g., age). For example, [29] applies kinematics analysis to extract features from driving data of several driving school instructors, general drivers, and elderly drivers when they drive passing urban intersections. It is shown that elderly drivers exhibit a common pattern that is different from young drivers.…”
Section: Related Workmentioning
confidence: 99%
“…The main drawback of using simulation data is that simulators cannot fully reflect the true driving condition. To collect driving data in practical traffic environments, carefully designed field-experiments are conducted in [23], [29], [40]. However, one potential issue of such methods is that drivers may be aware of the experiment purposes.…”
Section: A Naturalistic Driving Datasetmentioning
confidence: 99%